Retelling as a Strategy in Enhancing Students’ Reading Comprehension of Recount Text; A Classroom Action Research - Suriani Suriani; Melda Yeni (Jurnal Edukasi, 2023)
The goal of this study is to improve students' reading comprehension of recount text. It was implemented in the second grade of MTs Bustanul Ulum in Pekanbaru. This study included 30 students who had difficulty understanding recount text. As a result, the majority of them did not meet the English subject's minimum criteria. It seeks to determine whether the Retelling strategy can improve students' reading comprehension of recount texts, as well as what factors influence it. This was a two-cycle action research study. Each cycle included four meetings. The researcher and collaborator worked together to collect data through observation, field notes, tasks, tests, and interviews. The study discovered that implementing a retelling strategy could improve students' reading comprehension of recount text. This conclusion was reached based on an increase in the students' mean score in recount text reading comprehension tests from cycle I to cycle II. Furthermore, it was discovered that the material provided, the teacher's ability to guide and explain the material well, the students' motivation, and the appropriate strategy all influenced the change in students' reading comprehension of recount text. To summarize, the implementation of a retelling strategy improves second-year students' reading comprehension of recount text at MTs Bustanul Ulum, Pekanbaru